The Analysis of Factors Affecting the Buying Interest of E-Commerce Customers - Harisno, Harisno; Herby, Deborah (CommIT (Communication and Information Technology) Journal, 2018)
The goals of this research are to analyze factors affecting buying interest of e-commerce customers residing in the areas of Jakarta, Bogor, Depok, Tangerang, and Bekasi in Indonesia. A questionnaire is developed as the data acquisition instrument and is pretested by 30 respondents. The pretest is intended to evaluate the validity and reliability of the instrument. For the research, the data are collected from a random sample of 200 respondents. The research variables are ease of use, enjoyment, shopping experience, trust, promotion/advertising, and price. A structural equation model is established to assess the relations between the interested variables. As the results, the analysis shows that the factors of ease of use, promotion/advertising, and price significantly influence the buying interest. Meanwhile, the enjoyment, shopping experience, and trust do not affect the buying interest.